2018
DOI: 10.1016/j.enganabound.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the terms associated with ϕzz in free surface condition on the attitudes and resistance of different ships

Abstract: Citation: Li, Y., Gong, J., Ma, Q. ORCID: 0000-0001-5579-6454 and Yan, S. ORCID: 0000-0001- 8968-6616 (2018). Effects of the terms associated with phi(zz) in free surface condition on the attitudes and resistance of different ships. Engineering Analysis with Boundary Elements, 95, pp. 266-285. Abstract:One of approaches for numerical simulation of a ship moving in a still water is based on the composition of double-body flow and wavy flow solved by a boundary element method. There are several terms related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…The reasons behind this selection for the range of separation ratios were covering that of previous research into interference effects as well as some considerations in experiments. For instance, Zaghi, Broglia and Di Mascio [25] chose separation ratios between the two extremes of 0.167 and 0.3 whereas in some other cases separation ratios s/L of 0.226-0.470 [26], 0.15-0.81 [18], 0.2-0.5 [38], 0.2-1.0 [19,31], 0.12-0.39 [21], 0.2-0.4 [23], 0.17-0.23 [32], 0.2-0.8 [62], 0.2-0.5 [63], 0.2-0.4 [34], 0.226-0.4696 [28], 0.2-0.6 [29], and 0.09-0.5 [36] were investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons behind this selection for the range of separation ratios were covering that of previous research into interference effects as well as some considerations in experiments. For instance, Zaghi, Broglia and Di Mascio [25] chose separation ratios between the two extremes of 0.167 and 0.3 whereas in some other cases separation ratios s/L of 0.226-0.470 [26], 0.15-0.81 [18], 0.2-0.5 [38], 0.2-1.0 [19,31], 0.12-0.39 [21], 0.2-0.4 [23], 0.17-0.23 [32], 0.2-0.8 [62], 0.2-0.5 [63], 0.2-0.4 [34], 0.226-0.4696 [28], 0.2-0.6 [29], and 0.09-0.5 [36] were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Or even when there is a relative motion between two neighboring bodies, the slower one experiences stronger hydrodynamic loads as well as greater trim and sinkage due to the interaction [35]. In order to better capture the variations of trim and sinkage due to interference effect, Li, Gong, Ma and Yan [36] developed a fully nonlinear model of free surface based on boundary element method. Their findings showed that the smaller the separation ratio is, the more pronounced is the nonlinearity of the free surface.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical research of hydrodynamics of marine structures mainly adopts the potential flow CFD [16,17] and the viscous flow CFD method [18], which captures more details of the flow field. However, the computational efficiency of viscous flow CFD still needs to be improved, and a rapid thrust prediction method is required in the preliminary design stage for the waterjet ship.…”
Section: Introductionmentioning
confidence: 99%